Preparation and Characterization of bis (4-methoxyanilinium) tetrachlorozincate - Rahmouni, H.; Sta, W. Smirani; Rzaigui, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A new zinc complex of formula [C7H10NO]2 ZnCl4 has been prepared and characterized by X-ray diffraction,Â IR and UV-Visible spectroscopies. The complex crystallizes in the monoclinic space group P21/n with a minimal tetrahedral distortion of the ZnCl42- ion and with lattice parameters: a =12.054 (2) Ã…, b =7.129 (3) Ã…, c =23.480 (2) Ã…, Î² = 100.67 (2)Â°, V = 1983.03 (1) Ã…3 and Z = 4. The crystal structure was solved and refined to R = 0.080 and RW = 0.227 with 9611 independent reflections. It can be described by organic layers of p-anisidinium cations held together by C-Hâ€¦O hydrogen bonds parallel to (010) plane, linked to the inorganic groups of ZnCl42- anions through N-Hâ€¦Cl hydrogen bonds, electrostatic and Van Der Waals interactions, to form a three-dimensional network.